A New Code-Based Linkable Threshold Ring Signature Scheme - Ren, Fang; Xiu, Haiyan; Ji, Chuxin; Zheng, Dong; Wu, Ziyi (Wireless communications and mobile computing, 2022)
In this paper, we construct a new code-based linkable threshold signature scheme whose security is based on the hardness of the syndrome decoding problem and general syndrome decoding problem. We show that our scheme is secure in terms of existential unforgeability, anonymity, nonslanderability, and linkability. The complexity of the signature size proposed in this paper is Ot. Our method is particularly well suited for large free group voting systems. The greater the number of members in the ring, the more pronounced the advantage of the signature length is when compared to other schemes. That is, our scheme achieves a fixed length signature, independent of the number of ring members. In addition, our scheme has a very short public key, and the size is ON.